A cell-based smoothed three-node plate finite element with a bubble node for static analyses of both thin and thick plates - Thanh, Chau Dinh; Tuyen, Vo Ngoc; Phuc, Nguyen Hoang (Vietnam Journal of Mechanics, 2017)
This paper develops the cell-based (CS) smoothed finite element method for a three-node plate finite element with a bubble node at the centroid of the element. Based on the first-order shear deformation theory, the in-plane strains are smoothed on three non-overlapped subdomains of the element to transform the numerical integration of the element stiffness matrix from the surfaces into the lines of the subdomains. The shear-locking phenomenon, which occurs when the plate’s thickness becomes small, is removed by employing the mixed interpolation of tensorial components (MITC). The present element, namely CS-MITC3+, passes the patch test and behaves independently from the sequence of node numbers of the element. Numerical results given by the CS-MITC3+ elements are better than the MITC3+ elements. As compared to other smoothed three-node plate finite elements, the CS-MITC3+ is a good competitor.